2018
DOI: 10.1097/mao.0000000000002005
|View full text |Cite
|
Sign up to set email alerts
|

Nystagmus Findings and Hearing Recovery in Idiopathic Sudden Sensorineural Hearing Loss Without Dizziness

Abstract: Objectives: To investigate the incidence of nystagmus in patients with sudden sensorineural hearing loss (SSNHL) without dizziness, and to evaluate the correlation of the presence of nystagmus with hearing recovery in those patients. Study Design: Retrospective study. Setting: Tertiary referral academic medical center. Patients: Thirty-eight patients with SSNHL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Our patients showed very weak, persistent positional direction-changing nystagmus, of which the direction was geotropic in Case 1 and apogeotropic in Case 2. This type of positional nystagmus has been reported in other inner ear disorders [19][20][21][22][23][24], and it could not be clearly explained by typical BPPV [25]. The change in chemical composition and/or electrolyte concentration in the inner ear fluid, although still unclear, may underlie the production of this characteristic nystagmus in these patients.…”
Section: Discussionmentioning
confidence: 71%
“…Our patients showed very weak, persistent positional direction-changing nystagmus, of which the direction was geotropic in Case 1 and apogeotropic in Case 2. This type of positional nystagmus has been reported in other inner ear disorders [19][20][21][22][23][24], and it could not be clearly explained by typical BPPV [25]. The change in chemical composition and/or electrolyte concentration in the inner ear fluid, although still unclear, may underlie the production of this characteristic nystagmus in these patients.…”
Section: Discussionmentioning
confidence: 71%
“…The present study further revealed that OME or AOM patients without dizziness exhibited both irritative- or paretic-type direction-fixed nystagmus and direction-changing positional nystagmus. These various patterns of nystagmus have also been observed in various inner ear disorders such as Meniere’s disease, Ramsay Hunt syndrome, and sudden sensorineural hearing loss [ 23 , 28 30 ]. In AOM or OME, inflammatory mediators in the middle ear may penetrate into the inner ear space through the natural membranous barriers, which may cause damages to the hair cells or blood-perilymph barrier [ 3 , 31 ].…”
Section: Discussionmentioning
confidence: 94%
“…Findings of vestibular dysfunction including bithermal caloric results, spontaneous and positional nystagmus have been reported in limited number of adult AOM patients with vertigo [ 3 , 22 ], and the presence of dizziness or vertigo is considered indicative of one of the intratemporal complications of AOM. However, because dizziness is a subjective symptom defined as “a sensation of unsteadiness accompanied by a feeling of movement within the head” [ 23 ], the symptom threshold of dizziness may depend on individual’s sensitivity. Thus, patients with OME or AOM complicated by mild vestibular disturbance may not complain of dizziness symptom.…”
Section: Introductionmentioning
confidence: 99%
“…According to these studies, MD has various conditions of vestibular function in each stage of the illness, and HSN may reflect their reversibility. In ISSNHL, the presence of both vertigo 7 and nystagmus 8 can predict poor prognosis of hearing outcome. We examined HSN in cases of MD, which varied at different times according to the condition of the disease, and which may contribute to hearing prognosis.…”
Section: Relationship Between the Results Of The Head-shaking Test Anmentioning
confidence: 99%